Wood-Like Material from Thermoplastic Polymer and Landfill Bio-Materials: Dma, Tga and Solvent Resistance Properties. Issue 1 (February 2015) - Mousa, Ahmad; Heinrich, Gert; Wagenknecht, Udo
The aim of this work is to explore the potential application of chemically modified olive husk residue (OHR) as naturally occurring fillers to reinforce (Nylon-12) thermoplastic to produce a cost-effective wood like material. The Nylon-12/OHR composite material was fabricated via melt mixing of the Nylon-12 followed by the addition of chemically treated OHR at 180 and 50 rev.min −1 using Brabender internal mixer. The composites were characterized with respect to their dynamic mechanical properties, namely storage and viscous moduli (E′, E"), and mechanical loss factors (tan δ) using dynamic mechanical analyzer (DMA). The thermal stability of the samples with and without chemically treated OHR were examined using thermo-gravimetric analyzer (TGA). The chemical resistance of the composites was evaluated by immersing the samples in acidic and basic media and by exposing the samples to thermo-oxidative ageing (TOA) at 80C for 72h. The influence of TOA and immersion medium on the percentage weight loss, impact strength and hardness of the composites were reported. The effect of TOA and the solvent attack on the microstructure of the fractured samples was viewed by scanning electron microscope (SEM).